Informed choices for some, but not for others: An exploration of Australian midlife women’s participation in mammography screening by social class - Samantha Batchelor; Belinda Lunnay; Sara Macdonald; Paul R Ward (Women's Health)
Background: Population-level mammography screening for early detection of breast cancer is a secondary prevention measure well-embedded in developed countries, and the implications for women’s health are widely researched. From a public health perspective, efforts have focused on why mammography screening rates remain below the 70% screening rate required for effective population-level screening. From a sociological perspective, debates centre on whether ‘informed choice’ regarding screening exists for all women and the overemphasis on screening benefits, at the cost of not highlighting the potential harms. We dovetail these disciplinary agendas to contextualise the factors that impact mammography screening choices, interpreting screening status through a social class lens. Objective: To understand how social class impacts informed choice-making among midlife women (45–64 years), regarding (non) participation in mammography screening. Design: A qualitative study using semi-structured interviews. Methods: We interviewed 36 Australian midlife women from differing social class groups who were ‘screeners’ or ‘non-screeners’. We conducted a theory-informed thematic analysis and used Bourdieu’s relational social class theory to consider how women’s access to social, cultural and economic capital influenced their screening identities. We conducted matrix and crosstab queries across themes to identify patterns by social class. We extend the findings from Friedman’s study of women’s screening perspectives as ‘attentional’ types utilising the ‘sociology of attention’. Results: Our results map to Friedman’s four ‘attentional’ types (default or conscious interventionists, conflicted or conscious sceptics), and we show how social class impacts women’s attention to screening and participation. We show for middle-class women screening is a ‘given’, they align closely with normative screening expectations. Working-class women who screen, do so out of a sense of compliance. Affluent non-screeners make informed choices, while working-class women are more passive in their non-screening choices, being a group that sits outside of Friedman’s four attentional types. Conclusion: Current approaches to screening communication and programme delivery can be improved by tailoring approaches to reflect the impacts of social class in shaping women’s ’choices’. Subsequently, equitable breast cancer prevention may be afforded, which impacts positively on population-level screening rates.